2024
DOI: 10.3390/antiox13030300
|View full text |Cite
|
Sign up to set email alerts
|

Suppressing the Substance P-NK1R Signalling Protects Mice against Sepsis-Associated Acute Inflammatory Injury and Ferroptosis in the Liver and Lungs

Zhixing Zhu,
Stephen Chambers,
Madhav Bhatia

Abstract: Substance P (SP), encoded by the TAC1/Tac1 gene, acts as a significant mediator in dysregulated systemic inflammatory response and associated organ injury in sepsis by activating the neurokinin-1 receptor (NK1R). This study investigated the impact of SP-NK1R signaling on ferroptosis in the liver and lungs of mice with sepsis. Sepsis was induced by caecal ligation puncture (CLP) surgery in mice. The SP-NK1R signaling was suppressed by Tac1 gene deletion, NK1R blockade, and a combination of these two approaches.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(12 citation statements)
references
References 42 publications
0
1
0
Order By: Relevance
“…Additionally, ferroptosis inhibitors like Fer-1 and pioglitazone have been shown to reverse AKI damage in a mouse model by targeting ferroptosis, offering promising avenues for AKI treatment ( Hosohata et al, 2022 ). Acute liver injury is another condition with high clinical mortality rates, and recent studies have highlighted the potential of Nrf2 activation in mitigating liver injury ( Zhu et al, 2024 ). Furthermore, research by Yamada et al, 2020 indicated that upregulation of ferroptosis markers (iron ions, lipid peroxide levels) exacerbated liver injury in hepatic IRI models, but treatment with ferroptosis inhibitors like Fer-1 significantly reduced injury severity.…”
Section: Clinical Diseases Mediated By Ferroptosismentioning
confidence: 99%
“…Additionally, ferroptosis inhibitors like Fer-1 and pioglitazone have been shown to reverse AKI damage in a mouse model by targeting ferroptosis, offering promising avenues for AKI treatment ( Hosohata et al, 2022 ). Acute liver injury is another condition with high clinical mortality rates, and recent studies have highlighted the potential of Nrf2 activation in mitigating liver injury ( Zhu et al, 2024 ). Furthermore, research by Yamada et al, 2020 indicated that upregulation of ferroptosis markers (iron ions, lipid peroxide levels) exacerbated liver injury in hepatic IRI models, but treatment with ferroptosis inhibitors like Fer-1 significantly reduced injury severity.…”
Section: Clinical Diseases Mediated By Ferroptosismentioning
confidence: 99%
“…The mechanism leading to the dysregulated inflammatory response during sepsis remains poorly understood [ 4 ]. Substance P (SP), encoded by the tachykinin 1 ( Tac1 ) gene in rodents [ 5 ], has been demonstrated to be an important mediator contributing to the dysregulation of the acute inflammatory response in the liver and lungs of mice with sepsis [ 6 ]. The pro-inflammatory actions of SP in sepsis-associated acute liver and lung injury are mainly mediated by neurokinin-1 receptor (NK1R) [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Substance P (SP), encoded by the tachykinin 1 ( Tac1 ) gene in rodents [ 5 ], has been demonstrated to be an important mediator contributing to the dysregulation of the acute inflammatory response in the liver and lungs of mice with sepsis [ 6 ]. The pro-inflammatory actions of SP in sepsis-associated acute liver and lung injury are mainly mediated by neurokinin-1 receptor (NK1R) [ 6 ]. However, the precise mechanism leading to the detrimental effects of SP on sepsis remains to be investigated.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations